Role of high-mobility group box-1 in myocardial ischemia/reperfusion injury and the effect of ethyl pyruvate - LIN, YUNLING (Exp Ther Med, 2015)
High-mobility group box-1 (HMGB1) acts as a proinflammatory cytokine that triggers and amplifies the inflammation cascade following ischemia/reperfusion (I/R). Ethyl pyruvate (EP) has been reported to inhibit HMGB1 release in several I/R models. This study was designed to investigate the potential role of HMGB1 in a rat myocardial I/R model and to determine the effect of EP. Male Sprague Dawley rats were subjected to 30 min myocardial ischemia and 48 h reperfusion. In protocol 1, the rats were assigned to one of four groups (n=16 per group): Phosphate-buffered saline (PBS) or recombinant human HMGB1 (rhHMGB1) at three different doses (1, 10 or 100 μg/kg). In protocol 2, the rats were also assigned to one of four groups (n=16 per group): Sham, control, EP and EP + rhHMGB1. EP (40 mg/kg) or rhHMGB1 (100 μg/kg) was injected intravenously prior to reperfusion. Hemodynamic measurements were performed, and myocardial infarct size (IS) was calculated. Western blotting was conducted to evaluate HMGB1, tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) expression levels. In the protocol 1 rats, the IS was markedly increased in the rhHMGB1 (100 μg/kg) group compared with that in the PBS group, and this increase was accompanied by elevated levels of TNF-α and IL-6. In the protocol 2 rats, I/R resulted a 4.8-fold increase in HMGB1 expression with an increased IS and impaired cardiac function compared with the sham group. EP significantly inhibited the elevated HMGB1 level, suppressed the activated TNF-α and IL-6 and reduced cardiac dysfunction. This cardioprotection was abolished by rhHMGB1. In conclusion, accumulation of HMGB1 is deleterious to the heart following myocardial I/R. EP can exert a strong protective effect against myocardial I/R injury, and these benefits are associated with a reduction in HMGB1.